Month-of-Birth Effects on Skills and Skill Formation - Shintaro Yamaguchi; Hirotake Ito; Makiko Nakamuro (Institute of Labor Economics (IZA), 2023)
We estimate month-of-birth effects on cognitive and noncognitive skills, as well as factors relevant to skill formation. Our estimates indicate that younger students in a given grade cohort have lower cognitive and noncognitive skills. To shed light on the underlying mechanisms, we also examine children's time use and interpersonal relationships. We find evidence of compensatory investment in cognitive skills by younger children, however, they are also more likely to have poor-quality relationships with their classmates and teachers, which may harm the long-term development of noncognitive skills. Our findings on skill formation have implications for efficiency and equity.
Keywords: I20; I24; J24; 330; cognitive skill; relative age effect; noncognitive skill